Relationships between visibility and selected air pollutants in the Klang Valley - Jamal Hisham Hashim,; Zailina Hashim,; Azman Zainal Abidin, (Universiti Kebangsaan Malaysia, 1996)
Hazy conditions over the Klang Valley which last appeared in October 1991, began to reappear in August 1994. This study which was conducted during the beginning period of the haze episode, represents a preliminary attempt to identify the types of air pollutants that may be most associated with visibility reduction. Visibility and rainfall data were obtained from the Subang Airport Meteorological Station. The levels of selected air pollutants which include respirable particulated (PM10), nitrogen oxide, nitrogen dioxide, sulfur dioxide, carbon monoxide and ozone were measured from a station located at Dewan Bandaraya Kuala Lumpur. Data for visibility, rainfall and air pollutants were collected from August 1 to September 4, 1994, giving a total of 35 - 24 hour sampling days. On 2 of the 4 days with poor visibility, the Recommended Malaysian Air Quality Guidelines for PM10, nitrogen dioxide and sulfur dioxide were exceeded. Pearson correlation analysis showed statistically significant inverse correlations between visibility and PM10, nitrogen oxide, nitrogen dioxide and carbon monoxide, indicating pollutants from motor vehicles and other local combustion sources as important contributors to visibility reduction. A statistically significant inverse correlation between visibility and rainfall also indicates the ineffectiveness of light rain in despersing the haze. This study concludes that visibility in the Klang Valley may be worsening over the years; that local air pollution sources may play a much more important role in visibility reduction and the haze problem, than what might be realised; and that atmospheric PM10 may reach unhealthy levels at times. Comparison with other studies strongly support these conclusions.